The Contribution Of Creative Entrepreneurial Learning Outcomes, Emotional Intelligence, And The Implementation Of Tefa On The Entrepreneurial Interest Of Class XII - Rifka Jalal; Rijal Abdullah; Muhammad Adri; Risfendra Risfendra (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to examine the relationship between Productive Creative Entrepreneurship learning outcomes, emotional intelligence, and the implementation of the Teaching Factory on students’ entrepreneurial interest. The background of this research is based on the need to strengthen entrepreneurial spirit among vocational students to prepare them as job creators in an increasingly competitive labor market. Entrepreneurial interest is seen as a critical factor that determines students’ motivation and readiness to start a business after graduation. This research used a quantitative correlational approach involving 105 students of class twelve at SMKN 2 Gunung Talang. Data were collected through questionnaires and documentation, then analyzed using multiple linear regression techniques. The sampling technique used was proportional stratified total sampling 75 Students. The results showed a significant positive relationship between learning outcomes in Productive Creative Entrepreneurship and entrepreneurial interest (t = 2.418, p < 0.05), emotional intelligence and entrepreneurial interest (t = 6.309, p < 0.05), and Teaching Factory implementation and entrepreneurial interest (t = 4.420, p < 0.05). Furthermore, the joint analysis revealed that all three variables simultaneously had a significant influence on entrepreneurial interest (F = 21.897, p < 0.05). In conclusion, the study indicates that improving learning outcomes, emotional intelligence, and practical experience through Teaching Factory are crucial factors in fostering students’ interest in entrepreneurship. These findings suggest that a comprehensive educational approach integrating cognitive, emotional, and practical aspects is essential to prepare students to become successful young entrepreneurs.